Diagnostic and Management Considerations in a High-Risk Pregnant Patient With Ischemic Cardiomyopathy - Allison Bigeh, DO; Laxmi Mehta, MD; Lauren Lastinger, MD (JACC: Case Reports, 2024)
Ischemic heart disease is an important cause of heart failure in pregnancy. Involvement of a cardio-obstetrics team is crucial for managing high-risk pregnant patients with cardiovascular disease. We present a case of cardiogenic shock in a pregnant woman unmasking underlying multivessel obstructive coronary artery disease.